2018
DOI: 10.2147/ijnrd.s125942
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan in the treatment of autosomal dominant polycystic kidney disease: patient selection and special considerations

Abstract: Standard of care therapies for autosomal dominant polycystic kidney disease (ADPKD) may limit morbidity and mortality due to disease-related complications, but they do not delay disease progression. Tolvaptan, a selective vasopressin V2 receptor antagonist, delays the increase in kidney volume (a surrogate marker for disease progression), slows the decline in renal function, and reduces pain in ADPKD patients with relatively preserved renal function. The most common adverse events of tolvaptan are linked to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Both the major tolvaptan ADPKD trials (TEMPO38 and REPRISE39) demonstrated a significant risk of developing hepatotoxicity in 16 patients in the tolvaptan treatment group compared with 1 in the placebo group. The EMA have estimated a rare risk of severe hepatitis which may affect approximately 1 in 4000 ADPKD patients treated with tolvaptan 40…”
Section: Discussionmentioning
confidence: 99%
“…Both the major tolvaptan ADPKD trials (TEMPO38 and REPRISE39) demonstrated a significant risk of developing hepatotoxicity in 16 patients in the tolvaptan treatment group compared with 1 in the placebo group. The EMA have estimated a rare risk of severe hepatitis which may affect approximately 1 in 4000 ADPKD patients treated with tolvaptan 40…”
Section: Discussionmentioning
confidence: 99%
“…As liver function is preserved in PLD patients, we hypothesize that the risks of vaptans is lower in this group and its use for PLD‐related portal hypertension needs further investigation. However, the high cost of tolvaptan, which ranges between € 15 000 and € 30 000 per year, is a major barrier for widespread use …”
Section: Management Of Portal Hypertension In Pldmentioning
confidence: 99%
“…However, the high cost of tolvaptan, which ranges between € 15 000 and € 30 000 per year, is a major barrier for widespread use. [64][65][66] Lastly, large volume paracentesis (with or without albumin replacement) under radiological guidance should be used to achieve symptomatic relief, reduce fluid burden and alleviate abdominal distension. 15,45 The presence of spontaneous bacterial peritonitis, although infrequent, should be considered.…”
Section: Management Of Ascitesmentioning
confidence: 99%
“…Treatment with tolvaptan during early-stage chronic kidney disease (CKD) has been shown to slow total kidney volume growth and glomerular filtration rate (GFR) decline [ 10 ]. Based on clinical trial data, long-term treatment models indicate tolvaptan may delay ESRD by up to 6.5 years [ 12 ]. However, tolvaptan treatment can lead to hepatotoxicity and higher doses are not well tolerated due to a range of side effects, including aquaresis and polydipsia.…”
Section: Introductionmentioning
confidence: 99%